2020
DOI: 10.1186/s12885-020-6560-x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of self-expanding metallic stent placement followed by neoadjuvant chemotherapy and scheduled surgery for treatment of obstructing left-sided colonic cancer

Abstract: Background: This study aimed to evaluate the safety and feasibility of self-expanding metallic stent (SEMS) followed by neoadjuvant chemotherapy prior to elective surgery for obstructing left-sided colon cancer. Methods: Eleven consecutive patients with obstructing left-sided colon cancer between May 2014 and November 2015 were included retrospectively. All patients received SEMS followed by neoadjuvant chemotherapy. The primary outcome measure was stoma and laparoscopic surgery. Results: Chemotherapy was with… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 29 publications
(39 reference statements)
1
19
0
Order By: Relevance
“…In recent years, the detection of serum tumor markers in CC patients carries considerable implications for the diagnosis, assessment of therapeutic efficacy, and prognostic outcome of oncological disease in clinic. CEA and CA199 are frequently used as clinical markers for the assessment of oncological disease, and their levels may be utilized to identify the tumor staging as well as the prognosis of the patients [ 19 , 20 ]. In this study, the postoperative levels of CEA and CA199 were significantly lower in the combined group than in the surgical group, suggesting that preoperative neoadjuvant chemotherapy could be effective in improving the serum levels of CC patients, which in turn improved the prognosis of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the detection of serum tumor markers in CC patients carries considerable implications for the diagnosis, assessment of therapeutic efficacy, and prognostic outcome of oncological disease in clinic. CEA and CA199 are frequently used as clinical markers for the assessment of oncological disease, and their levels may be utilized to identify the tumor staging as well as the prognosis of the patients [ 19 , 20 ]. In this study, the postoperative levels of CEA and CA199 were significantly lower in the combined group than in the surgical group, suggesting that preoperative neoadjuvant chemotherapy could be effective in improving the serum levels of CC patients, which in turn improved the prognosis of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…As previously described, 11 SEMS (WallFlex; Boston Scientific Corporation, Natick, MA, USA) was inserted under fluoroscopic guidance. Stent expansion and position were confirmed with abdominal radiography.…”
Section: Methodsmentioning
confidence: 99%
“…The use of neoadjuvant chemotherapy after SEMS placement in patients with potentially curable obstructive colon cancer is rare. Only one retrospective analysis with a small sample size ( n = 9) was found[ 73 ]. In this study, the efficacy and safety of SEMS insertion followed by neoadjuvant chemotherapy and elective surgery were evaluated, and the study results revealed relatively low toxicity, high adherence to two to three cycles of neoadjuvant chemotherapy before elective surgery and no evidence of perineural invasion in resected specimens[ 73 ].…”
Section: Application Of Neoadjuvant Systemic Chemotherapy In Obstructive Colon Cancermentioning
confidence: 99%
“…Only one retrospective analysis with a small sample size ( n = 9) was found[ 73 ]. In this study, the efficacy and safety of SEMS insertion followed by neoadjuvant chemotherapy and elective surgery were evaluated, and the study results revealed relatively low toxicity, high adherence to two to three cycles of neoadjuvant chemotherapy before elective surgery and no evidence of perineural invasion in resected specimens[ 73 ]. The authors suggested that neoadjuvant chemotherapy may lower the risk of perineural invasion, possibly improving survival outcomes[ 73 ].…”
Section: Application Of Neoadjuvant Systemic Chemotherapy In Obstructive Colon Cancermentioning
confidence: 99%
See 1 more Smart Citation